One Health surveillance approaches for melioidosis and glanders: The Malaysian perspective - Mariappan, Vanitha; Vellasamy, Kumutha Malar; Anpalagar, Rohan Raaj; Lim, Yue-Min; Zainal Abidin, Nurhamimah; Subramaniam, Sreeramanan; Nathan, Sheila (Frontiers in Veterinary Science, 2022)
The One Health concept was initiated to promote the integration of human, animal, and environmental ecosystems into healthcare to ensure effective control and the sustainable governance of multifaceted health matters. Climate change, deforestation, and rigorous farming disrupt the environment, which serves as the natural habitat for many animals and microbes, increasing the likelihood of disease transmission between humans and animals. Melioidosis (neglected tropical diseases) and glanders are of humans and animals caused by the gram-negative bacteria Burkholderia pseudomallei and its close relative Burkholderia mallei, respectively. In Malaysia, although melioidosis is endemic, it is not a notifiable disease. Hence, the true prevalence of melioidosis in Malaysia is unknown and varies in different regions of the country, with reported hotspots associated with agriculture-related activities. To date, no incidence of human glanders has been reported in Malaysia, although occupational exposure for equine handlers and veterinary professionals remains a concern. Additionally, antibiotics are widely used in the healthcare and veterinary sectors to treat or prevent B. pseudomallei and B. mallei infections, leading to the emergence of resistance in B. pseudomallei. Lack of surveillance, research, assessment, and management of glanders and melioidosis is a major issue in Malaysia. Proper assessment systems and cross-discipline cooperation are vital to recognize and manage both diseases. Experts and practitioners from clinical and veterinary disciplines, environmentalists, law enforcement, policymakers, researchers, local communities, and other experts need to communicate, collaborate, and coordinate activities to fill the knowledge gap on glanders and melioidosis to reduce morbidity and mortality rates in the country. This review aims to define the organizational and functional characteristics of One Health surveillance approaches for glanders and melioidosis from a Malaysian perspective.